UPAYA MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA MELALUI MODEL PEMBELAJARAN PRACTICE REHEARSAL PAIRS PADA PEMBELAJARAN PRAKTIK PEMESINAN KELAS XI TMB SMK BHINNEKA KARYA SURAKARTA - Arseta Budi Utomo; Danar Susilo Wijayanto; Basori Basori (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2019)
The research is intended to improve successfully learning motivation and achievement in Mechanical Engineering B, 11th grade at vocational high school of Bhinneka Karya Surakarta in Machinery Practical Learning using Practice Rehearsal Pairs learning model. The research is Classroom Action Research that conducted in two cycles. Each cycle consisted of four stages, there are: planning, acting, observing, and reflecting. The instruments to collect the data, there are questionnaire, interview, test, observation, and documentation. The data was carried out using descriptive qualitative analysis. The result of research showed that there is an improvement in students’ learning motivation and achievement. The student’ learning motivation increased from 74.5% in cycle 1 to 92.59% of students having learned motivation belonging to minimally good category in cycle 2. The students’ cognitive learning achievement increased from 66.67% to 88.89%, the affective learning achievement increased from 81.48% to 85.19%, and the psychomotor learning achievement of students increased from 74.07% to 88.89% of students who could achieve MPC.